2016
DOI: 10.5194/piahs-373-209-2016
|View full text |Cite
|
Sign up to set email alerts
|

Inflow forecasting using Artificial Neural Networks for reservoir operation

Abstract: Abstract. In this study, multi-layer perceptron (MLP) artificial neural networks have been applied to forecast one-month-ahead inflow for the Ubonratana reservoir, Thailand. To assess how well the forecast inflows have performed in the operation of the reservoir, simulations were carried out guided by the systems rule curves. As basis of comparison, four inflow situations were considered: (1) inflow known and assumed to be the historic (Type A); (2) inflow known and assumed to be the forecast (Type F); (3) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Luk et al, [50], have applied the three types of ANNs, namely Multilayer Feed forward Neural Networks, Partial Recurrent Neural Networks and Time Delay Neural Networks for prediction of Rainfall forecasting and found that the ANN gives better result than other models. Khalili et al, [40], have utilized ANN (Artificial Neural Network) modeling with a new approach like three-layer feed-forward perceptron network with back propagation algorithm to predict daily rainfall forecasting. Further they have also described about hidden dynamics of rainfall through the past information of the system and concluded that the used model is best for daily rainfall forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Luk et al, [50], have applied the three types of ANNs, namely Multilayer Feed forward Neural Networks, Partial Recurrent Neural Networks and Time Delay Neural Networks for prediction of Rainfall forecasting and found that the ANN gives better result than other models. Khalili et al, [40], have utilized ANN (Artificial Neural Network) modeling with a new approach like three-layer feed-forward perceptron network with back propagation algorithm to predict daily rainfall forecasting. Further they have also described about hidden dynamics of rainfall through the past information of the system and concluded that the used model is best for daily rainfall forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have applied data-driven models to water-quality simulations, runoff forecasting, water level forecasting, wind speed forecasting, etc. [19][20][21][22][23]. Maniquiz et al [24] used multiple linear regression (MLR) to establish an equation for estimating pollutant load with rainfall as a variable, indicating that total rainfall and average rainfall intensity can be used as predictors of pollutant load.…”
Section: Introductionmentioning
confidence: 99%
“…e SVM [11,12] and the SVR [13,14] have been used in the field of streamflow forecasting research. It is important to remark that the artificial neural networks (ANN) represent the most widely applied artificial intelligence techniques for modelling [15][16][17], and it has been widely used in hydrology [18][19][20]. e backpropagation neural network (BPNN) is the improvement of the ANN learning representations by error backpropagation algorithm, which is the most popular neural network.…”
Section: Introductionmentioning
confidence: 99%